Experimental characterization and comparison of performance parameters of S-rotors for standalone wind power system - Bhayo, B.A. (Elsevier Ltd, 2017)
An open wind flow test of seven Savonius models was conducted to explore the influence of design parameters on the performance and starting characteristics. The seven rotors are coded as Model 1 to Model 7, with various blade designs, number of blades, and number of stages. Results demonstrated that Model 1, a modified two-blade single-stage conventional S-rotor, has the highest power coefficient of 0.26. Model 1 also exhibited an improved maximum power coefficient of about 47 than the previously reported in the literature due to increasing of the aspect ratio from 0.77 to 2.0. The power coefficient of double-stage Savonius-rotors was found to be lower by about 11–20 than the identical design single-stage S-rotors. The static torque assessment exhibited that double-stage rotors and rotor with more than three blades do not have any negative torque angle position. Nonetheless, the single-stage Savonius-rotor, even with three blades, has few negative torque angles. The study suggests that Model 2, modified double-stage rotor and Model 5, conventional double stage rotor with overlap ratio of 0.2, are most suitable rotors for stand-alone wind power systems, where they have not shown any negative torque angle, in spite that the power coefficient can be sacrificed for the sake of improved starting ability. © 2017 Elsevier Ltd